Process management in organizations - a discussion on terminology - Winiarska, Magdalena; Kizielewicz, Joanna (Zielona Góra: Faculty of Economics and Management Press)
In the literature on the subject, one can notice quite a lot of freedom in the approach to formulating and understanding of terms relating to process orientation, process approach and managing processes and process management. In recent years, there has been a noticeable increase in interest in the study of process management not only of organizations, but also of individual activities such as projects.
Keywords: process management; process approach; process orientation